The Wheat Lr67 Gene from the Sugar Transport Protein 13 Family Confers Multipathogen Resistance in Barley. Issue 4 (9th October 2018) - Milne, Ricky J.; Dibley, Katherine E.; Schnippenkoetter, Wendelin; Mascher, Martin; Lui, Andy C.W.; Wang, Lanxiang; Lo, Clive; Ashton, Anthony R.; Ryan, Peter R.; Lagudah, Evans S.
Abstract : The Lr67res multipathogen resistance gene from wheat confers resistance to barley-specific pathogens when transformed into barley. Abstract: Fungal pathogens are a major constraint to global crop production; hence, plant genes encoding pathogen resistance are important tools for combating disease. A few resistance genes identified to date provide partial, durable resistance to multiple pathogens and the wheat ( Triticum aestivum ) Lr67 hexose transporter variant (Lr67res) fits into this category. Two amino acids differ between the wild-type and resistant alleles – G144R and V387L. Exome sequence data from 267 barley ( Hordeum vulgare ) landraces and wild accessions was screened and neither of the Lr67res mutations was detected. The barley ortholog of Lr67, HvSTP13, was functionally characterized in yeast as a high affinity hexose transporter. The G144R mutation was introduced into HvSTP13 and abolished Glc uptake, whereas the V387L mutation reduced Glc uptake by ∼ 50%. Glc transport by HvSTP13 heterologously expressed in yeast was reduced when coexpressed with Lr67res . Stable transgenic Lr67res barley lines exhibited seedling resistance to the barley-specific pathogens Puccinia hordei and Blumeria graminis f. sp. hordei, which cause leaf rust and powdery mildew, respectively. Barley plants expressing Lr67res exhibited early senescence and higher pathogenesis-related ( PR ) gene expression. Unlike previous observations implicating flavonoids in the resistance of transgenic sorghum ( Sorghum bicolor ) expressing Lr34res, another wheat multipathogen resistance gene, barley flavonoids are unlikely to have a role in Lr67res-mediated resistance. Similar to observations made in yeast, Lr67res reduced Glc uptake in planta . These results confirm that the pathway by which Lr67res confers resistance to fungal pathogens is conserved between wheat and barley.